The Effect of Natural Graphite Pretreatment on Electrochemical Behavior of Graphene Oxide - Kozlica, Dž.; Pljuco, S.; Metarapi, D.; Korać, F.; Gutić, S. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Irreversible electrochemical behavior of graphene oxide, prepared by oxidation and exfoliation via the improved Hummers method, was compared for natural graphite flakes with particle size below 40 μm and between 40 and 50 μm, with and without treatment with hydrofluoric acid. It is shown that the highest relative increase in capacitance occurs upon electrochemical reduction of HF-pretreated graphite flakes with particle size below 40 μm. Capacitance follows a sharp increase and subsequent gradual decrease with increment of cathodic polarization. Obtained results are discussed in terms of higher accessible surface area, irreversible reduction of oxygen groups contributing to pseudocapacitance, and the increase of conductivity upon restoration of the delocalized π electron system.